Implementational Aspects of the Contourlet Filter Bank and Application in Image Coding. (2nd February 2009) - Nguyen Nguyen, Truong T. Truong T.; Liu Liu, Yilong Yilong; Chauris Chauris, Hervé Hervé; Oraintara Oraintara, Soontorn Soontorn
Abstract : This paper analyzed the implementational aspects of the contourlet filter bank (or the pyramidal directional filter bank (PDFB)), and considered its application in image coding. First, details of the binary tree-structured directional filter bank (DFB) are presented, including a modification to minimize the phase delay factor and necessary steps for handling rectangular images. The PDFB is viewed as an overcomplete filter bank, and the directional filters are expressed in terms of polyphase components of the pyramidal filter bank and the conventional DFB. The aliasing effect of the conventional DFB and the Laplacian pyramid to the directional filters is then considered, and the conditions for reducing this effect are presented. The new filters obtained by redesigning the PDFBs satisfying these requirements have much better frequency responses. A hybrid multiscale filter bank consisting of the PDFB at higher scales and the traditional maximally decimated wavelet filter bank at lower scales is constructed to provide a sparse image representation. A novel embedded image coding system based on the image decomposition and a morphological dilation algorithm is then presented. The coding algorithm efficiently clusters the significant coefficients using progressive morphological operations. Context models for arithmetic coding are designed to exploit the intraband dependency and the correlation existing among the neighboring directional subbands. Experimental results show that the proposed coding algorithm outperforms the current state-of-the-art wavelet-based coders, such as JPEG2000, for images with directional features.